State Revenue (Tax System and Policies, Shifting of the Tax Burden, Welfare Lost Due to Tax) - Suyanto (LPPI Universitas Al-Qolam Malang, 2021)
Government revenue is the revenue received and used by the government to carry out its functions so that it can independently pay for its increased spending in the public sector. Taxes are usually a country's main source of income, funding national development and government spending. The purpose of this research is to find out how tax codes and tax politics operate, as well as how the tax burden has changed and how much wealth has been lost as a result of taxation. Tax is an obligation that must be paid by a person or entity to the state which is imposed by law, has no direct reciprocity, and is used for governmental purposes in the interests of the people. In tax collection, there are three systems. Taxation politics in Indonesia are regulated in 10 laws, and changes to the tax burden are divided into two parts. The excess burden imposed by the tax is referred to as the welfare lost due to taxation. Key words: economic; revenue; system; tax; welfare